2017
DOI: 10.1016/j.contraception.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Levonorgestrel butanoate intramuscular injection does not reliably suppress ovulation for 90 days in obese and normal-BMI women: a pilot study

Abstract: Background We performed a pilot evaluation of a new formulation of levonorgestrel butanoate (LB) designed to be a long-acting injectable (6 months) contraceptive to determine pharmacodynamic end-points in normal and obese BMI women. Study design Obese (BMI ≥ 30 kg/m2) and normal BMI, otherwise healthy, women received a single intramuscular injection of LB after ovulation was confirmed in a baseline cycle. The primary outcome was return of ovulation in days. Results A total of 14 women enrolled and complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…LB underwent several clinical trials but to this date has not been marketed [12] . A more recent study [13] found that a higher body mass index of women resulted in earlier return to ovulation, suggesting possible inconsistencies in efficacy from woman to woman.…”
Section: Introductionmentioning
confidence: 98%
“…LB underwent several clinical trials but to this date has not been marketed [12] . A more recent study [13] found that a higher body mass index of women resulted in earlier return to ovulation, suggesting possible inconsistencies in efficacy from woman to woman.…”
Section: Introductionmentioning
confidence: 98%